The nucleolus from a liquid droplet perspective. (6th August 2021) - Yoneda, Mitsuhiro; Nakagawa, Takeya; Hattori, Naoko; Ito, Takashi
Abstract: The nucleolus is a membrane-less organelle sequestered from the nucleus by liquid droplet formation through a liquid–liquid phase separation (LLPS). It plays important roles in cell homoeostasis through its internal thermodynamic changes. Reversible nucleolar transitions between coalescence and dispersion are dependent on the concentrations, conformations and interactions of its molecular liquid droplet-forming components, including DNA, RNA and protein. The liquid droplet-like properties of the nucleolus enable its diverse dynamic roles. The liquid droplet formation mechanism, by which the nucleolus is sequestered from the nucleoplasm despite the absence of a membrane, explains a number of complex nucleolar functions. Graphical Abstract: